Retinal Vessel Analysis as a Novel Screening Tool to Identify Childhood Acute Lymphoblastic Leukemia Survivors at Risk of Cardiovascular Disease. Issue 6 (August 2020) - Azanan, Mohamad S.; Chandrasekaran, Sudhashini; Rosli, Erda S.; Chua, Ling Ling; Oh, Lixian; Chin, Tong Foh; Yap, Tsiao Yi; Rajagopal, Revathi; Rajasuriar, Reena; MacGillivray, Tom; Trucco, Emanuele; Ramli, Norlina; et al.
Abstract : Background: Microvascular endothelial dysfunction is central to the pathogenesis of cardiovascular disease (CVD). The eye offers direct access for endothelial health assessment via the retinal microvasculature. The aim of the study was to investigate whether image-based retinal vessel analysis is a feasible method of assessing endothelial health in survivors of childhood acute lymphoblastic leukemia (cALL). Materials and Methods: Cardiovascular risk factors (CRFs) were estimated using the 30-year Framingham Risk Score in 73 childhood leukemia survivors (median age: 25; median years from diagnosis: 19) and 78 healthy controls (median age: 23). Radial arterial stiffness was measured using pulse wave analyzer, while endothelial activation markers were measured by soluble intercellular adhesion molecule 1 (sICAM-1) and soluble vascular cell adhesion molecule 1 (sVCAM-1). Retinal fundus images were analyzed for central retinal artery/vein equivalents (CRAE/CRVE) and arteriolar-venular ratio (AVR). Results: cALL survivors had higher CRF ( P <0.0001), arterial stiffness ( P =0.001), and sVCAM-1 ( P =0.007) compared with controls. Survivors also had significantly higher CRVE ( P =0.021) while AVR was significantly lower ( P =0.026) in survivors compared with controls, compatible with endothelial dysfunction. In cALL survivors with intermediate risk for CVD, CRAE, and AVR are significantly lower, while sVCAM-1 and sICAM-1 are significantly higher when compared with survivors with low CVD risk after adjusting with covariates (age, sex, and smoking status). Conclusions: cALL survivors have an increased risk of CVD compared with age-matched peers. The survivors demonstrated microvasculopathy, as measured by retinal vascular analysis, in addition to physical and biochemical evidence of endothelial dysfunction. These changes predate other measures of CVD. Retinal vessel analysis may be utilized as a robust screening tool for identifying survivors at increased risk for developing CVD. Abstract : Supplemental Digital Content is available in the text.